Effectiveness and safety of community-based treatment with sofosbuvir plus ribavirin for elderly patients with genotype 2 chronic hepatitis C. Issue 9 (September 2017) - Atsukawa, Masanori; Tsubota, Akihito; Kondo, Chisa; Shimada, Noritomo; Abe, Hiroshi; Kato, Keizo; Okubo, Tomomi; Arai, Taeang; Itokawa, Norio; Iio, Etsuko; Tanaka, Yasuhito; Iwakiri, Katsuhiko
Abstract: Background: The aim of this study was to clarify the effectiveness and safety of sofosbuvir/ribavirin therapy for elderly patients with genotype 2-infected chronic hepatitis C (CHC) in Japan. Methods: A multicenter, retrospective study evaluated the effectiveness and safety of sofosbuvir/ribavirin based on real-world clinical data. Results: The subjects consisted of 270 patients, 47.0% of whom were aged ≥65 years. The sustained virological response rates in patients aged <65 and ≥65 years were 98.6% and 95.3%, respectively. Hemoglobin levels decreased during treatment due to ribavirin-related hemolysis, and were significantly lower in patients aged ≥65 years than those aged <65 years at all time-points. A reduction in ribavirin dose was necessary in 31.0% (26/84) of patients with hemoglobin levels <13.0 g/dL and in 70.7% (39/127) of those aged >65 years. Although the most frequent adverse event was anemia, no patients discontinued the use of either ribavirin or sofosbuvir. The incidence of ribavirin-related anemia in patients aged ≥65 years was 34.6% and significantly higher compared with that in patients aged <65 years (2.8%). Conclusions: Treatment with sofosbuvir/ribavirin for genotype 2-infected CHC was effective and safe even for elderly patients, although the incidence of adverse events including ribavirin-related anemia was relatively high.